The somatic affairs of BRAF: tailored therapies for advanced malignant melanoma and orphan non-V600E (V600R-M) mutations. Issue 5 (5th March 2013) - Ponti, Giovanni; Pellacani, Giovanni; Tomasi, Aldo; Gelsomino, Fabio; Spallanzani, Andrea; Depenni, Roberta; Al Jalbout, Samer; Simi, Lisa; Garagnani, Lorella; Borsari, Stefania; Conti, Andrea; Ruini, Cristel; et al.
Abstract : BRAF V600R-M-D are uncommon mutations, not included in the experimental protocols of BRAF selective inhibitors. We report the evaluation of correlations among different types of BRAF somatic mutations in melanoma and their management with BRAF inhibitors. 21 patients with BRAF mutated metastatic melanoma were enrolled in the protocol with BRAF inhibitors for compassionate use at the University of Modena. Hot spot V600E mutations were found in 19 patients. V600R mutation and double (V600E -V600M) mutation were identified in two melanomas. In one case, V600K mutation was found. Two screening failures were noted. Mean progression free survival at follow-up of to 8 weeks, was 7.6 months. Five patients had a very short follow-up and the experimental protocol is still ongoing, so we cannot provide complete follow-up data. However, all of them are still under treatment and disease progression free. An objective response with few side effects was observed in all patients. in vitro studies with the aim of testing drug sensitivity.